2008
DOI: 10.1634/stemcells.2007-0832
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Maintains the Neurogenic Capacity of Embryonic Neural Progenitor Cells In Vitro but Changes Their Neuronal Subtype Specification

Abstract: Many in vitro systems used to examine multipotential neural progenitor cells (NPCs) rely on mitogens including fibroblast growth factor 2 (FGF2) for their continued expansion. However, FGF2 has also been shown to alter the expression of transcription factors (TFs) that determine cell fate. Here, we report that NPCs from the embryonic telencephalon grown without FGF2 retain many of their in vivo characteristics, making them a good model for investigating molecular mechanisms involved in cell fate specification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 89 publications
(129 reference statements)
2
27
0
Order By: Relevance
“…We investigated also the D-V identity that results altered under in vitro culture conditions, thus confirming the FGF-2 ventralizing activity [18][19][20]. We found that NS cells show a general expression of intermediate and ventral genes, such as Olig2, Meis2 and Ascl1 (although a neocortical-VZ expression is present for the latter [29]).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We investigated also the D-V identity that results altered under in vitro culture conditions, thus confirming the FGF-2 ventralizing activity [18][19][20]. We found that NS cells show a general expression of intermediate and ventral genes, such as Olig2, Meis2 and Ascl1 (although a neocortical-VZ expression is present for the latter [29]).…”
Section: Discussionsupporting
confidence: 66%
“…We also showed that different NS cell lines maintain a region-specific pattern of transcription factors that is stable for over 20 passages in culture. On the other hand, the D-V identity is affected by in vitro culture conditions, thus confirming FGF-2 ventralizing activity [18][19][20]. Furthermore, we provide evidence that the donor developmental stage is critical for the derivation of committed NS cells that maintain an in vitro positional identity consistent with that of the region of derivation.…”
Section: Introductionsupporting
confidence: 73%
“…Recently, techniques have been established for reliably generating monolayers of induced pluripotent stem cell (iPSC)‐derived NSCs using supplementation with basic fibroblast growth factor (FGFb) and epidermal growth factor (EGF) 54, 55, 56. However, such cultured monolayer NSCs are more transcriptionally homogeneous than in vivo NSCs, and it has been speculated that this lack of heterogeneity is responsible, at least in part, for the challenges of promoting the differentiation of cultured NSCs into diverse neuronal subtypes 56, 57, 58, 59…”
Section: Discussionmentioning
confidence: 99%
“…These steps will affect the properties of GRP relative to the original progenitor population present in vivo or relative to cells isolated acutely and used without culturing or exogenous manipulation. 45 Consequently, cell stocks designed for clinical applications require extensive characterization following grafting in terms of their therapeutic efficacy as well as their safety. Indeed, this work continues a series of studies testing the properties of hGRP prepared by Q-therapeutics in models of amyotrophic lateral sclerosis, 46 inflammatory demyelination, 14 and spinal cord …”
Section: Haas and Fischermentioning
confidence: 99%